Covalent binding of flavonoids with silk sericin hydrolysate: Anti‐inflammatory, antioxidant, and physicochemical properties of flavonoid–sericin hydrolysate conjugates. Issue 7 (21st March 2022) - Omar, Adil; Wali, Ahmidin; Arken, Amina; Gao, Yanhua; Aisa, Haji Akber; Yili, Abulimiti
Abstract: To construct food ingredients with improved bioactivities and physicochemical properties, two sericin hydrolysate–flavonoid conjugates, bearing quercetin and rutin covalently bound to sericin, were prepared under alkaline conditions. UV spectroscopy and SDS‐PAGE confirmed that sericin hydrolysate and oxidized flavonoids formed conjugates, which were primarily the result of covalent interactions. Changes and differences in molecular weight distribution, secondary and tertiary structures, surface hydrophobicity, and surface morphology were observed. Anti‐inflammatory activities were evaluated by basing on inhibitory activity against nitric oxide (NO) production and 15‐lipoxygenase (15‐LOX). The conjugates showed significantly improved ( p  < .05) anti‐inflammatory and emulsifying properties than unmodified sericin hydrolysate. Meanwhile, the covalent interaction had a positive effect on the antioxidant activity of sericin hydrolysate. Practical applications: We had prepared flavonoid–sericin hydrolysate conjugates and evaluated the effect of covalent binding of flavonoids on the physicochemical, anti‐inflammatory, antioxidant, and emulsifying properties of sericin hydrolysate, which is beneficial to broaden the range of applications of sericin and flavonoids in the food, cosmetics, and pharmaceutical industries. Abstract : Under alkaline conditions, two sericin hydrolysate‐flavonoid conjugates were prepared. Alterations in molecular weight distribution, secondary and tertiary structures, surface hydrophobicity, and surface morphology were observed. Compared to unmodified sericin hydrolysate, the sericin hydrolysate‐flavonoid conjugates showed improved emulsifying, anti‐inflammatory, and antioxidant properties.